A Look at How Philosophical Perspectives of Adult Education Shape the Practice at Universidad Nacional, Costa Rica - Barrantes-Elizondo, Lena (2022)
Introduction. Looking close at the philosophical orientation of institutions and educators allows the examination of whether teaching practice, in this case, higher education, is consistent with the purpose of education. Objective. In the interest of gaining a historical understanding of the role of the Universidad Nacional, Costa Rica (UNA) in adult education in Costa Rica, this essay aims to analyze philosophical perspectives by drawing on relevant written documentation. Discussion. This institution is currently one of the five public universities in Costa Rica and has a robust student funding system. Under its necessary university principle, students with different economic and social statuses have access to high-quality post-secondary education. Having a clear educational philosophy is vital as it helps examine the educators’ and the institution’s practice critically. This essay gives a broader understanding of the philosophical perspectives behind the teaching and learning practices proposed by UNA’s core guideline, the Pedagogical Model (PM). Conclusions. As final conclusions, it can be stated that this institution has lost its driving humanistic perspective, established in the first Organization Statute. In addition, on a sad note, Nuñez’s founding philosophical orientation and goals for UNA are partially accomplished since even though there is an accessible education for all, teaching and learning practices do not guarantee any commitment to social action and social reform.